Pengaruh Disiplin Kerja, Beban Kerja, dan Kompensasi Terhadap Kinerja Guru Bahasa Inggris Kota Banjarmasin - Axnes Leadyani Saputri; Edison C Sembiring; Jamalullail; Nafiah Ariyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The quality of education in Indonesia is still said to be low. Based on phenomena in the field, it was found that (1) learning planning (RPP) had not been created optimally because RPPs were made in a copy paste culture; (2) in implementing learning, some teachers still predominantly use conventional methods such as the lecture method, the learning process is boring and students become passive; (3) in implementing learning, some teachers have not used various media. The aim of this research is to analyze the influence of work discipline, workload and compensation on the performance of high school English teachers in Banjarmasin City, both partially and simultaneously. The type of research used is a quantitative research method with a sample size of 60 respondents. Data collection methods are by means of questionnaires, interviews and document studies. The data analysis includes variable measurement, descriptive data analysis, data analysis with SEM PLS, model measurement, and hypothesis testing. The research results show that work discipline and workload have a significant effect on the performance of English teachers in Banjarmasin City, while compensation does not have a significant effect on the performance of English teachers in Banjarmasin City. Work Discipline, Workload and Compensation simultaneously influence and contribute to Teacher Performance (Y) by 54.3%.